A multi-stage and multi-supplier inventory model allowing different order quantities - Chang, Shu-Chin; Chang, Ching-Ter (Applied Mathematical Modelling, 2017)
•A multi-stage inventory model is presented with multiple suppliers subject to a set of constraints.•This proposed model allows different order quantities/intervals for each selected supplier.•The cost of unequal-order quantity allocation is lower than that of equal-order quantity allocation. This paper addresses a multi-stage inventory model that allows different order quantities among the selected suppliers to obtain the optimal solutions. To achieve the objective of the study, the single-objective and multi-objective methods are adopted for suitable real-world applications. With respect to a single-objective method, this paper aims to minimize the total ordering costs, holding costs, and purchasing costs, subject to the price, quality, and capacity. With respect to a multi-objective method, it focuses on cost minimization, as well as quality and capacity maximization. The proposed model not only considers the allocation of different order quantities among the selected suppliers, but also incorporates the multi-stage inventory problem. Furthermore, a numerical example is provided to illustrate the usefulness of the proposed model and a comparative understanding of various methods. In addition, a simulation test is performed to effectively validate the proposed model which outperforms the previous works. Finally, a sensitivity analysis is carried out to investigate the impact of supply chain cost.